Developing English Reading Skills of the Students of Business Administration at Private Universities in Bangladesh: Prospects and Problems - Mirza, Md Golam Hoshain (Journal of Business and Technology (Dhaka), 2012)
This paper examines the efforts of the English language teachers who are working to develop English reading skills among the students studying in the Business Administration departments at ten of the English-medium private universities in Bangladesh. Adopting both the quantitative and the qualitative approaches, it analyses the data collected through student interview-schedule. The study identifies that, in spite of having good classroom facilities and necessary supplementary materials, the reading classes are not as effective as they could be. It is mainly because unsuitable materials are inappropriately used in a class of students with significantly different levels of proficiency. The paper finally suggests some measures that can be taken to make the reading class more effective. Among others, it recommends that the English teacher should involve first the university administration in forming the language class with students of similar proficiency level and then the BBA teachers in developing appropriate materials for it. DOI: http://dx.doi.org/10.3329/jbt.v5i2.9989 Journal of Technology (Dhaka) Vol. 5(2), July-December, 2010 180-190